Analisis Strategi Pemasaran Sebagai Strategi Persaingan Bisnis: Studi Kasus Bisnis Kuliner Rumah Makan Talago Biru di Kota Pekanbaru - Cindy Fredicia Putri; Atika Fitriani; Devinda Ramdani; Aisyah Rahmatul Fitri; Dian Puji Puspita Sari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to analyze marketing strategies as an effort to increase the competitiveness of the Talago Biru restaurant business in Pekanbaru City. The research method used is descriptive with a qualitative approach. Data was collected through semi-structured interviews using an interview guide as the main tool for collecting information. The research results show that Talago Biru has succeeded in implementing effective marketing strategies to expand their target market and maintain business competitiveness. This strategy includes market segmentation based on geographic and demographic criteria, determining appropriate target markets, as well as using a comprehensive marketing mix (product, price, place and promotion). Supporting factors in implementing this strategy include consistent product quality, service that satisfies customers, and complete business licensing. However, there are also inhibiting factors such as limited raw materials and tight market competition. This study provides an in-depth understanding of how marketing strategies can be a crucial factor in increasing business competitiveness in the culinary industry.